Lubyanka's Nightingale and the Novel That Exposed CIA Operation TRIGON. Issue 4 (2nd October 2021) - Fischer, Benjamin B.
Abstract: When Yuri Andropov offered to divulge how the Komitet Gosudarstvennoy Bezopasnosti (KGB) foiled an important Central Intelligence Agency (CIA) operation, Julian Semyonov ("Lubyanka's nightingale") jumped at the chance to write a spy thriller based on real people and events. TASS is Authorized to Announce … (1979) is a fictional version of a CIA operation involving Soviet diplomat Aleksandr Ogorodnik (a.k.a. TRIGON). The novel confirms Director of Central Intelligence Stansfield Turner's suspicion that Ogorodnik was a KGB dangle whose rumored suicide was false. It also foreshadowed the KGB's bogus claim that the CIA was an accessory to Ogorodnik's murder of his mistress. Andropov sponsored the work of fiction as a subtle way of revealing clues that he had outfoxed the Agency.